An Overview of Immunomodulatory Activity of Rasayanas (International Journal of Ayurveda and Pharma Research, 2024)
The term "immunomodulation" refers to the regulation and modulation of immunity, which may be accomplished by either enhancing or suppressing the immune response. A medication with immunomodulatory activity has particular importance given in the current state of pandemics, the rise in antibiotic resistance, and autoimmune diseases. A medicine with immunomodulatory properties that enhance quality of life would be great. Here lies the importance of Rasayana tantra which consists of many formulations aiming at increasing the quality of life by imparting longevity, memory, disease-free life, youth, excellence of body, and sense organs. Many Rasayanas have been shown to have immunomodulatory properties. Rasayanas have a calming effect on the psyche in addition to its intended benefits for physical health. It has also been demonstrated that stress affects immunity. Several Rasayanas have been shown to exhibit anti-stress properties. Rasayana may thus strengthen the psycho-neuro-immune axis and control the immune system by utilising the body's warriors, such as phagocytes and cytokines. Research on Rasayanas such as Amalaki rasayana, Triphala rasayana, Chyavanaprasha, etc. has been conducted both in vitro and in vivo. These kinds of studies establish the system as evidence-based and shed some light on the mechanism of action. The present review will provide knowledge about immunomodulatory activity and the action mechanism of Amalaki rasayana, Triphala rasayana, Rasayana choorna, Shatavari Medhya rasayana and Chyavanaprasha.